The Urals and Western Siberia in the Bronze and Iron ages - koryakova, ludmila (Cambridge University, 2013)
This book is the first synthesis of the archaeology of the Urals and Western Siberia. It presents a comprehensive overview of the late prehistoric cultures of these regions, which are of key importance for the understanding of long-term changes in Eurasia.